Panduan RDA Malaysia - Anisatul-Wahidah Abdul Wahid; Perpustakaan Negara Malaysia . Pusat Bibliografi Negara (Kuala Lumpur : Perpustakaan Negara Malaysia, 2014)
Guidelines on descriptive cataloging for libraries in Malaysia
Includes bibliographical references (pages 301-302)
Keywords: Descriptive cataloging -- Standards; Descriptive cataloging -- Standards -- Malaysia; Descriptive cataloging -- Malaysia -- Handbooks, manuals, etc